Wittgenstein's metaphilosophy - Horwich, Paul (Clarendon Press, 2012)
A bold interpretation of Ludwig Wittgenstein's later work. It argues that it is Wittgenstein's radically anti-theoretical metaphilosophy - and not his identification of the meaning of a word with its use - that underpins his discussions of specific issues concerning language, the mind, mathematics, knowledge art, and religion.